2011
DOI: 10.1007/s11420-010-9188-6
|View full text |Cite
|
Sign up to set email alerts
|

A Pre-Clinical Test Platform for the Functional Evaluation of Scaffolds for Musculoskeletal Defects: The Meniscus

Abstract: In an attempt to delay the progression of osteoarthritis from an index injury, early intervention via repair of injured musculoskeletal soft tissue has been advocated. Despite the development of a number of scaffolds intended to treat soft tissue defects, information about their functional performance is lacking. The goal of this study was to consolidate a suite of in vitro and in vivo models into a pre-clinical test platform to assess the functional performance of meniscal repair scaffolds. Our objective was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 35 publications
(48 reference statements)
1
21
0
1
Order By: Relevance
“…To our knowledge, the only previous assessment of a scaffold's ability to restore contact stresses in the knee involved Actifit . In these studies, Actifit restored mean contact pressure to intact levels, but peak contact pressure increased by 36% and contact area decreased by 20%, relative to the intact knee, similar to the results with our scaffold.…”
Section: Discussionsupporting
confidence: 77%
“…To our knowledge, the only previous assessment of a scaffold's ability to restore contact stresses in the knee involved Actifit . In these studies, Actifit restored mean contact pressure to intact levels, but peak contact pressure increased by 36% and contact area decreased by 20%, relative to the intact knee, similar to the results with our scaffold.…”
Section: Discussionsupporting
confidence: 77%
“…[5][6][7] A biomechanical analysis showed that the Actifit implant restores contact mechanics. 8 For total meniscus replacements, a caprolactone-urethanebased scaffold appeared mechanically too weak to cope with the high forces in the joint, and cartilage degradation was not prevented. 9,10 Tissue engineering would potentially resolve the problem of scaffolds that are initially too weak to be implanted.…”
Section: Introductionmentioning
confidence: 99%
“…Já, os scaffolds possuem como intuito restaurar as funções do menisco pelo crescimento tissular no interior de sua estrutura (21). Atualmente existem dois tipos de scaffolds empregados em cirurgias: o implante meniscal de colágeno (CMI®, Menaflex) e o implante de poliuretano (Actifit®), ambos são temporários e comercias na Europa para substituição meniscal parcial (lateral e medial) (14,28,(35)(36)(37). Também está em análise clinica o Nusurface® para substituição meniscal medial total (8,9,28).…”
Section: Capítulo 10unclassified